Engineered Cell Membrane-Derived Nanocarriers: The Enhanced Delivery System for Therapeutic Applications - Yu, Biao; Xue, Xu; Yin, Zhifeng; Cao, Liehu; Li, Mengmeng; Huang, Jianping (Frontiers in Cell and Developmental Biology, 2022)
There has been a rapid development of biomimetic platforms using cell membranes as nanocarriers to camouflage nanoparticles for enhancing bio-interfacial capabilities. Various sources of cell membranes have been explored for natural functions such as circulation and targeting effect. Biomedical applications of cell membranes-based delivery systems are expanding from cancer to multiple diseases. However, the natural properties of cell membranes are still far from achieving desired functions and effects as a nanocarrier platform for various diseases. To obtain multi-functionality and multitasking in complex biological systems, a wide variety of functionalized modifications of cell membranes is being developed based on physical, chemical, and biological methods. Notably, at the interface of multi-technologies and cell membranes, many research opportunities have been initiated, opening a promising frontier in therapeutic applications. Herein, the current exploration of natural cell membrane functionality, the design principles for engineered cell membrane-based delivery systems, and the disease applications are reviewed, with a special focus on the emerging strategies in engineering approaches.